Islamic critique of religious fetishism - Hashi, Abdurezak Abdulahi (2008)
Contemporary discussion about ‘religious fetishism’ includes two interrelated themes. First is the concept of religious fetishism itself which is associated to the tribal religions and totems who worshipped ‘an inanimate object for its magical power’ or the belief in the soul of the departed coming to dwell in anything that is tangible in heavens which require religious veneration. Second is the belief of modern scholars of sociology and psychology of religion that ‘religious fetishism’ is one of the earliest and the most primordial religious beliefs of man, followed by belief in demons, polytheism and finally monotheism. However, while the first theme is about human religious tendency to consecrate the natural phenomenon, the later theme is about the rudimentary genesis of monotheism in relation to polytheism throughout the course of human history. The question is whether or not the primordial faith of man was monotheistic, and later developed into polytheism? Though with a different perspective, both themes are among theological focus points of both the Qur’an and Islamic theology. This paper uses analytical and comparative methods to present an Islamic critique of religious fetishism.